2006
DOI: 10.1002/ccd.20628
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of staple‐mediated femoral arteriotomy closure: Results from a randomized multicenter study

Abstract: Compared to manual compression, the EVS device provides a safe and effective method of femoral artery closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Should most patients undergoing femoral arterial access get a VCD? For diagnostic cases, the answer may be "yes" based upon both decreased complication rates and improved time to ambulation (1,4,8,16,54). As outlined in the preceding text, however, there are numerous subgroups of diagnostic patients for whom insufficient data are available to make a clear recommendation.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Should most patients undergoing femoral arterial access get a VCD? For diagnostic cases, the answer may be "yes" based upon both decreased complication rates and improved time to ambulation (1,4,8,16,54). As outlined in the preceding text, however, there are numerous subgroups of diagnostic patients for whom insufficient data are available to make a clear recommendation.…”
Section: Discussionmentioning
confidence: 94%
“…This review will focus on the immediate, active hemostasis closure devices given their greater utilization over the past decade. The adoption of VCD has occurred because of a clear technological feat: VCD reliably shortens the time to hemostasis (elapsed time between sheath removal and first observed hemostasis) compared with manual compression and thus allows earlier patient ambulation (1,8,10,16,17) ( Table 2). Alternative strategies for achieving early ambulation are the use of smaller sheaths for diagnostic catheterization as well as the use of the radial artery approach.…”
Section: Vcds: the First Decadementioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the use of VCDs, in contrast to manual compression, decreases the time to ambulation and hemostasis. [1][2][3] Unfortunately, VCD adverse events can occur with significant short-and long-term implications. [4][5][6][7][8] There are currently no prospective randomized trials to show a reduction in arterial-related events comparing standard compression therapy and VCDs.…”
mentioning
confidence: 98%